Biodegradable Polymers: A Patch of Detachable Hybrid Microneedle Depot for Localized Delivery of Mesenchymal Stem Cells in Regeneration Therapy (Adv. Funct. Mater. 23/2020). (4th June 2020) - Lee, KangJu; Xue, Yumeng; Lee, Junmin; Kim, Han‐Jun; Liu, Yaowen; Tebon, Peyton; Sarikhani, Einollah; Sun, Wujin; Zhang, Shiming; Haghniaz, Reihaneh; Çelebi‐Saltik, Betül; Zhou, Xingwu; et al.
Abstract : In article number 2000086, KangJu Lee, Ali Khademhosseini, and co‐workers present a novel device for enhancing wound healing, the detachable hybrid microneedle depot. It is the first device to use a microneedle array to facilitate localized mesenchymal stem cell delivery with a minimal dose of cells.